THE ROLES OF SOCIAL MEDIA MARKETING, LIFESTYLE AND CONSUMER ETHNOCENTRISM IN ENHANCING BRAND AWARENESS AND PURCHASE INTENTION - Yanto Marfi; Ayu Wukir Permata; Rini Setiowati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study examines the influence of social media marketing activities (entertainment, informativeness, trendiness, and interactivity), lifestyle, and consumer ethnocentrism on brand awareness, the effect of brand awareness on purchase intention and the mediating role of brand awareness in the relationship between those factors and consumers purchase intention in the Indonesian skincare market. A quantitative research approach was adopted, using primary data collected from 161 respondents. The proposed hypotheses were tested using Structural Equation Modeling (SEM) with SmartPLS version 4.0. The findings reveal that entertainment, informativeness and trendiness significantly enhance brand awareness, whereas interactivity, lifestyle and consumer ethnocentrism do not exhibit significant effects. Additionally, brand awareness demonstrates a significant impact on purchase intention and serves as an effective mediator between entertainment, informativeness and trendiness and purchase intention. Overall, these results emphasize the strategic value of creating engaging, informative and trend-relevant social media content to strengthen brand awareness and stimulate consumer purchasing behavior within the skincare industry.